Unified low‐layer power allocation and high‐layer mode control for video delivery in device‐to‐device network with multi‐antenna relays. Issue 10 (1st July 2016) - Wang, Qin; Wang, Wei; Jin, Shi; Zhu, Hongbo; Zhang, Nai Tong
Abstract : This study proposes a quality‐driven approach that jointly selects the frequency reuse mode of device‐to‐device (D2D) links at lower layers, the video coding mode of frames, and multiple paths at higher layers for multimedia transmission in a cellular network with multi‐antenna relays placed at the intersection of adjacent cells. Based on power control of the shared relay, the user‐centered mode selection problem is formulated by maximising the quality of service (QoS) with total energy consumption constrained. Underlay mode and overlay mode are both considered. For each frame, one coding mode (I, P, or B) and multiple paths (cellular links and/or D2D links with/without relays) are selected to optimise the received video quality expectation. Different retransmission polices are considered to give higher protection levels to paths with higher transmission rates. The authors' evaluation shows that the proposed unified power allocation and mode control scheme could enhance the perceived QoS as changing the energy constraint and the distances of different paths. The underlay mode is optimal in most cases. It provides evidences that it is not always the best to code all frames as I‐frames, to initialise the relay transmission power as the maximum, or to select one single path for video transmission.